Longitudinal causal impacts of preschool teacher training on Ghanaian children's school readiness: Evidence for persistence and fade‐out. Issue 5 (2nd July 2019) - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Peele, Morgan
Abstract: Preschool programs have expanded rapidly in low‐ and middle‐income countries, but there are widespread concerns about whether they are of sufficient quality to promote children's learning and development. We conducted a large school‐randomized control trial ('Quality Preschool for Ghana' – QP4G) of a one‐year teacher training and coaching program, with and without parental‐awareness meetings, designed to improve preschool quality and child development. We followed 3, 435 children in 240 schools in the Greater Accra Region of Ghana, a country with universal pre‐primary education. A previous study reported positive impacts of teacher training (but not teacher training plus parental‐awareness meetings) at the end of the implementation year on some dimensions of classroom quality, teacher well‐being, and children's school readiness (Wolf et al., [2019] Journal of Research on Educational Effectiveness, 12, 10–37). The present study analyzed a new round of data collected 1 year after the end of implementation to assess (a) the extent of persistence in impacts on child development and (b) whether such impacts vary by select child, household, and school characteristics. We found impacts of the teacher training intervention on children's overall school readiness were sustained ( d  = 0.13), but were only marginally statistically significant. When broken down by domain, impacts on social–emotional skills specifically persisted. Persistent negative effects of teacher training plus parental‐awareness meetings varied by the literacy status of the male parent such that negative impacts were concentrated in children in households with non‐literate male heads. Abstract : This study analyzed year two impacts on child school readiness from a school‐randomized trial of a one‐year preschool teacher training and coaching program, with and without parental‐awareness meetings, in Ghana. We found impacts of the teacher training intervention on children's overall school readiness were sustained, and were driven by sustained impacts on social‐emotional skills specifically.